ANTI-CRISIS FINANCIAL MANAGEMENT BY ENTERPRISES IN MODERN CONDITIONS - Азаренкова, Галина; Свередюк, Катерина; Омеляненко, Денис (Socio-economic relations in the digital society, 2019)
The article describes the essence of anti-crisis management as a component of general management of the enterprise and an integral system, which consists of principles, methods of development and implementation of a complex of special management decisions. The purpose of anti-crisis management, tasks that will help to achieve it and the principles that underlie the implementation of anti-crisis measures are set out. The following principles are set: the principle of constant preventive action and readiness for response, urgency and adequacy of response, complexity of decisions, alternative of actions and management adaptability, priority of use of internal resources, optimization of external sanation and principle of effi ciency. The problems of enterprises in a crisis state, periodically or permanently failing to continue normal production and economic activity and to pay their bills are investigated. Th e reason for the emergence in the Ukrainian economy of the need for new tools for managing enterprises in a crisis, which can detect and neutralize the root causes of crisis processes, is explained. An example of the Public Joint Stock Company «Kharkiv Tile Factory» investigated the fi nancial analysis of the enterprise and outlined the main principles of anti-crisis management. Th e author’s view on the mechanism of crisis management is presented, its essence and components are defi ned, the sequence of stages of implementation of anti-crisis management at this enterprise is described. It is concluded that one of the most important tasks of the company’s anti-crisis policy is the strategic management of innovations, the implementation of which largely depends on the quality of the adoption of innovative solutions, the ability to fi nd solutions that can be organizationally and economically able to achieve the goal.